Strengthening Sustainability in the Steel Industry - World Bank (World Bank, Washington, DC, 2022)
People have used steel since ancient times, after blacksmiths discovered that iron became harder and stronger after being placed in charcoal furnaces. Today, steel is present in virtually every aspect of people's lives, from homes and hospitals to roads and other infrastructure that provide the foundation for social and economic development. Steel is among the world's most recycled materials, with circular economy practices incorporated into various stages of the production cycle. Yet the high-temperature heat vital to its production process still requires large amount of energy. Hence, the iron and steel sector remains among the largest consumers of energy and emitters of carbon dioxide, accounting for 6 to 7 percent of global greenhouse gas emissions.' With growing global concerns over climate change, regulators, investors, and industrial customers are increasingly pushing steelmakers to increase their sustainability by pursuing decarbonization pathways. To speed up the process will require incremental and breakthrough technologies, and the International Finance Corporation has been exploring opportunities to finance such projects and support steelmakers to become more sustainable.